Preparation and characterization of plasma treated PP composite electrolyte membranes - Bae, B; Chun, BH; Ha, HY; Oh, IH; Kim, D (ELSEVIER SCIENCE BV, 2002)
Methanol impermeable thin polymer electrolyte membrane,; were prepared by impregnating Nafion((R)) solution in porous polypropylene (PP) membranes for direct methanol fuel cell application. In order to enhance the impregnation amount and stability of Nafion((R)) molecules, not only the solvent in commercial Nafion((R)) solution was exchanged with ethanol, but the surface and pores of PP membranes ere treated with Freon-116 plasma gas. The proton conductivities of the prepared Nafion((R))/PP composite membranes were about 10 times lower, but the resistance to methanol permeability was about 10 times higher than those of commercial Nafion((R)) membrane,. The impregnation features of Nafion((R)) molecules in the plasma treated and non-treated membrane pores were compared by examining the cross-sectional morphologies of membranes. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: PROTON-EXCHANGE MEMBRANES; IONOMERIC MEMBRANES; METHANOL CROSSOVER; FUEL-CELLS; TRANSPORT